Is adherence to dialectic behaviour therapy for post-traumatic stress disorder (PTSD) and cognitive processing therapy related to treatment outcome in PTSD after childhood abuse? - Steil, Regina; Weiß, Judith; Müller-Engelmann, Meike; Dittmann, Clara; Priebe, Kathlen; Kleindienst, Nikolaus; Fydrich, Thomas; Stangier, Ulrich (European journal of psychotraumatology, 2023)
Background: Literature on the association between therapist adherence and treatment success in the treatment of post-traumatic stress disorder (PTSD) is scarce, and the results are mixed. Objective: To examine the relationship between therapist adherence to dialectical behaviour therapy for PTSD (DBT-PTSD) and cognitive processing therapy (CPT) on treatment outcome in women with PTSD and emotion regulation difficulties after interpersonal childhood abuse. Method: Videotaped therapy sessions from 160 female participants of a large randomized controlled trial [Bohus, M., Kleindienst, N., Hahn, C., Müller-Engelmann, M., Ludäscher, P., Steil, R., Fydrich, T., Kuehner, C., Resick, P. A., Stiglmayr, C., Schmahl, C., & Priebe, K. (2020). Dialectical behavior therapy for posttraumatic stress disorder (DBT-PTSD) compared with cognitive processing therapy (CPT) in complex presentations of PTSD in women survivors of childhood abuse. JAMA Psychiatry, 77(12), 1235. jamapsychiatry.2020.2148] were rated. Adherence to CPT and DBT-PTSD was assessed using two specifically developed rating scales. Results: Higher therapist adherence was associated with a greater reduction of clinician-rated PTSD symptom severity. This effect was more pronounced in the CPT group than in the DBT-PTSD group. Adherence was also related to a greater reduction of self-rated PTSD symptoms, borderline symptoms, and dissociation intensity. Conclusion: Our results indicate that higher therapist adherence can lead to better treatment outcomes in PTSD treatments, especially in CPT. Higher therapist adherence to cognitive processing therapy was associated with higher treatment gains in women with post-traumatic stress disorder (PTSD) after childhood abuse.Adherence was related to higher reductions in symptom severity of PTSD, borderline symptoms, and dissociation intensity.Adherence to dialectical behaviour therapy for PTSD did not show a strong association with treatment outcome. Higher therapist adherence to cognitive processing therapy was associated with higher treatment gains in women with post-traumatic stress disorder (PTSD) after childhood abuse. Adherence was related to higher reductions in symptom severity of PTSD, borderline symptoms, and dissociation intensity. Adherence to dialectical behaviour therapy for PTSD did not show a strong association with treatment outcome.
Online veröffentlicht: 20. Okt. 2023
Gesehen am 20.02.2024